Editorial: proton pump inhibitor use in cirrhosis—a piece of the puzzle. Authors' reply. Issue 5 (10th February 2021) - Rocco, Alba; Compare, Debora; Sgamato, Costantino; Coccoli, Pietro; Nardone, Gerardo
Abstract : LINKED CONTENT This article is linked to Rocco et al and Celsa & Cammà papers. To view these articles, visit https://doi.org/10.1111/apt.16239 and https://doi.org/10.1111/apt.16250